Sistem Pakar Diagnosa Penyakit Kardiovaskular Menggunakan Metode Certainty Factor - Ajisari, Lanang Dian; Prasetyaningrum, Putri Taqwa (APTIKOM SUMSEL, 2024)
Cardiovascular disease is the main cause of death globally causing challenges in the world of health, including in Indonesia. Lack of public knowledge about cardiovascular disease is very dangerous if preventive measures are not taken immediately. Currently, the treatment of cardiovascular disease is done manually, takes a long time, costs a lot and the practice hours of cardiologists are short. To overcome this problem, researchers implemented an expert system that can diagnose cardiovascular disease and a web system is needed to identify symptoms and apply the certainty factor method as a decision-making tool in overcoming public uncertainty in early examinations. This system involves 6 disease data, 29 symptom data, and 20 case data. In this study, testing was carried out based on the results of expert validation with accuracy system test data, resulting in an appropriate level of symptom and disease compliance and an accuracy level of 100% obtained from 20 data checks.